Entrained flow Co-gasification of torrefied biomass and coal - ÖZDOĞAN, ZEYNEP SİBEL (My University, 2023)
© 2022 Elsevier LtdIn this study, the effect of blending selected torrefied biomass and lower-rank coal samples on entrained flow co-gasification is experimentally investigated, and the results are compared with entrained flow gasification of coal samples. Three biomass samples were torrefied in a lab-scale torrefaction system to obtain a coal-like structure, coherent with the selected coal samples. 275 °C and 40 min were selected as the best-suited torrefaction condition for blending with the coal samples. Four 1:1 coal-torrefied biomass blends were prepared considering the ash and grindability properties for entrained flow co-gasification. The gasification simulations were carried out with Aspen HYSYS to assess the effect of the process conditions. The entrained flow gasifier with 15 kW capacity was built and operated between 1500 °C and 1200 °C with three coals and their four blends. The experimental results show methane (>1300 °C gasification temperature) and tar-free syngas composition. The results of entrained flow co-gasification experiments indicate higher cold gas efficiencies, better syngas quality, and carbon conversion with torrefied biomass blending compared to entrained flow gasification of coal samples. Co-utilization of coal and biomass can be part of a short to medium-term contribution to energy, waste, and global climate change problems.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; İnşaat Mühendisliği; Yapı; Matematik; Bilgisayar Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Civil Engineering; Structure; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Mühendislik; Sosyal Bilimler Genel; MÜHENDİSLİK, MEKANİK; MÜHENDİSLİK, ÇEVRE; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; İNŞAAT VE YAPI TEKNOLOJİSİ; MATEMATİK, UYGULAMALI; ÇEVRE ÇALIŞMALARI; MÜHENDİSLİK, İMALAT; MÜHENDİSLİK, İNŞAAT; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); ENGINEERING; MATHEMATICS; SOCIAL SCIENCES, GENERAL; ENGINEERING, MECHANICAL; ENGINEERING, ENVIRONMENTAL; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; CONSTRUCTION & BUILDING TECHNOLOGY; MATHEMATICS, APPLIED; ENVIRONMENTAL STUDIES; ENGINEERING, MANUFACTURING; ENGINEERING, CIVIL; İnşaat ve Yapı Mühendisliği; Fizik Bilimleri; Modelleme ve Simülasyon; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yapı ve inşaat; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Kirlilik; Makine Mühendisliği; Genel Enerji; Yönetim, İzleme, Politika ve Hukuk; Endüstri ve İmalat Mühendisliği; Elektrik ve Elektronik Mühendisliği; Civil and Structural Engineering; Physical Sciences; Modeling and Simulation; Renewable Energy, Sustainability and the Environment; Building and Construction; Fuel Technology; Energy Engineering and Power Technology; Pollution; Mechanical Engineering; General Energy; Management, Monitoring, Policy and Law; Industrial and Manufacturing Engineering; Electrical and Electronic Engineering; Biomass; Co-gasification; Entrained bed gasifier; Low-rank coals; Torrefaction